КУЛЬТУРНАЯ КОННОТАЦИЯ ФРАЗЕОЛОГИЗМОВ РУССКОГО ЯЗЫКА - ЗИМИН, ВАЛЕНТИН (Studia Rossica Posnaniensia, 2006)
Cultural connotation is a manifestation of culture in the semantic content of phraseological units. There is no direct correlation between culture and language because the presupposition (previously known immense knowledge) always takes its place between them and serves as the key for the interpretation of both. It is impossible to comment on the cultural content of phraseological units not knowing their presuppositional base. That is why the cultural commentary of phraseological units is nothing else but methodical disclosure of their presuppositional aspects which are the true codes of culture and include in themselves meanings and senses connected with mythology, legends, rites and rituals, symbols, stereotypes, traditions, habits and so on.